2008
DOI: 10.1111/j.1472-8206.2008.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive effects of crude extracts from leaves of Echinodorus grandiflorus

Abstract: The antihypertensive action of a crude ethanolic extract (EEEG) from leaves of Echinodorus grandiflorus (Alismataceae) was investigated in spontaneously hypertensive rats. The intraperitoneal injection of increasing doses of EEEG (300-1000 mg/kg) elicited dose-dependent reductions in mean arterial pressure (MAP) that were paralleled by reductions of cardiac output and systemic vascular resistance, reaching the maximum of 23 +/- 5%, 13 +/- 3% and 18 +/- 4%, respectively (n = 5, P < 0.05). Comparable reductions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 29 publications
0
15
0
2
Order By: Relevance
“…Brugiolo et al (2011) showed that the extract of E. grandiflorus was able to modulate allergic pulmonary inflammation, and it may also be useful as a potential therapeutic agent for asthma (Lessa et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Brugiolo et al (2011) showed that the extract of E. grandiflorus was able to modulate allergic pulmonary inflammation, and it may also be useful as a potential therapeutic agent for asthma (Lessa et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The prominent BP profile and magnitude was that of atropine ( figure 4.44 a). Infusion of agonists was done 20 minutes after infusing atropine in most studies in which atropine was used to block the muscarinic receptors (Muntzel et al, 1997;Dimo et al, 2003;Delphine Holopherne et al, 2008;Khwanchuea et al, 2008;Lessa et al, 2008;Liu et al, 2008;Rattmann et al, 2008;Shirasaka et al, 2009;De Menezes et al, 2010). violacea were significantly (p < 0.05) higher than those observed with muscarine after pretreatment of animals with atropine.…”
Section: Does T Violacea Act By Blocking the Beta I Adrenoceptors?mentioning
confidence: 99%
“…The bradykinin system regulates sodium water balance, renal and cardiac haemodynamics, and BP by mediating and modulating a) the vasoconstricting RAAS; and b) the vasodilating prostaglandin, prostacyclin, adrenomedullin and NO. Reduced activity of the system has been reported in various hypertensive situations in both clinical and experimental models of HTN (Lessa et al, 2008;De Leo et al, 2009;Günthner et al, 2009;Sharma, 2009;Bakris, 2010;Hanif et al, 2010).…”
Section: The Bradykinin Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the aqueous leaf extract was examined after administration of the muscarinic receptor antagonist, atropine (2 mg/kg), the beta-adrenoceptor antagonist, propranolol (1 mg/kg), the histamine H 1 receptor agonist, mepyramine (5 mg/kg), or the nitric oxide synthase inhibitor, N ω -nitro-l-arginine methyl ester (l-NAME, 5 mg/kg) (Weldon et al, 1995;de Moura et al, 2005;Ghayur et al, 2005;Lessa et al, 2008;Diaz-Juarez et al, 2009). Each drug was given intravenously and allowed to incubate for 5 min before a bolus injection of 19.41 mg/kg (ED 50 ) A. muricata extract was infused.…”
Section: Effect Of a Muricata On Atropine Propranolol Histamine Anmentioning
confidence: 99%